Establishing Monitored Premises Status for Continuity of Business Permits During an HPAI Outbreak - Umber, Jamie; Johnson, Rebecca; Kromm, Michelle; Linskens, Eric; Culhane, Marie R.; Goldsmith, Timothy; Halvorson, David; Cardona, Carol (Frontiers in Veterinary Science, 2018)
Recent experiences with avian influenza outbreaks in poultry in the United States have tested biosecurity protocols and outbreak management strategies. During an outbreak, regulatory officials managing the emergency response need to make timely decisions in order to achieve disease control and eradication goals while simultaneously decreasing the unintended consequences of the response. To move susceptible animals or animal products out of a disease Control Area via a secure food supply continuity of business (COB) permit without the risk of expanding a disease outbreak, premises must be designated as Monitored Premises (MP) by regulatory officials. The experience of and lessons learned from the 2014 to 2015 highly pathogenic avian influenza (HPAI) outbreak have resulted in defined criteria necessary to establish MP status during an HPAI outbreak and highlighted the need for a clear method to determine that those criteria have been met. Establishing MP status is different from an epidemiologic investigation, though they both require analyses of how avian influenza virus may enter poultry premises and can take significant staff time. MP status of premises seeking to move animals or animal products must be continuously re-evaluated as Infected Premises status, and resulting epidemiologic contacts, can rapidly change during an outbreak. We present here a questionnaire to establish MP status, designed to be initially completed by industry representatives in an attempt to streamline processes and conserve resources. During an outbreak, the MP status questionnaire is an essential risk-based management tool used to establish premises status, as part of operationalizing permitted movement to support COB.